ANALYSIS OF DIET CARBOHYDRATE LOADING ON LACTIC ACID LEVELS, BLOOD GLUCOSE LEVELS AND PERFORMANCE OF ROWING ATHLETES AT 2000 METER DISTANCE - Fadhiil, Fahmi
Background: Storage of carbohydrates in the body is very limited, which is only about 350-500 grams or can provide energy of 1,200-2,000 kcal. This storage can be increased by increasing the consumption of carbohydrates. Glucose is a compound that is the main source of energy for the body. The stability of blood glucose levels is very important to support performance during high-intensity matches which can lead to a decrease in glycogen stores and cause hypoglycemia. Accumulation of lactic acid in the blood becomes a fundamental problem in physical performance, because it causes chronic fatigue and decreases physical performance, so that it can interfere with athlete performance when competing or exercising. Method: The subjects in this study were rowing athletes in West Bandung Regency, 11 people, the study used clinical trials. The parameters measured were lactic acid levels, blood glucose levels, the performance of rowing athletes at a distance of 2000 meters and calculating the amount of basal energy BMR (Basal Metabolic Rate) and TDEE (Total Daily Energy Expenditure) as ingredients to determine the number of daily food calories in rowing athletes. Results: there was a significant change (p<0.05) between pre-test-test, post and after 15'm blood lactic acid levels and blood glucose levels on treatment diet. There was no significant difference (p> 0.05) on normal diet anddiet carbohydrate loading on body weight and performance of athletes rowing a distance of 2000 meters. Meanwhile, the energy of male rowing athletes in West Bandung Regency shows an average BMR (Basal Metabolic Rate) is (1,687 ± 97.8) and the mean TDEE (Total Daily Energy Expenditure) is (3374 ± 195.6). Conclusion:diet carbohydrate loading is able to delay fatigue and is able to maintain blood glucose levels quite well when compared to a normal diet. While the results of the performance of rowing athletes at a distance of 2000 meters and body weight during this study there was no significant difference (p <0.05), but the interaction on rowing athletes' performance was better when compared to a normal diet.